Uji Aktivitas Antikolesterol Kombinasi Ekstrak Teh Oolong, Buncis Dan Kayu Manis - Ahmad Fauzi; Tanti Azizah Sujono; Azis Saifudin; Arifah Sri Wahyuni (Universitas Muhammadiyah Surakarta, 2022)
Hyperlipidemia has an important role in the occurrence of cardiovascular, cerebrovascular, and peripheral vascular diseases. High cholesterol and LDL levels in the blood are at risk of causing various diseases such as atherosclerosis, pancreatic dysfunction and kidney disorders. Meanwhile, high triglyceride levels can cause impaired liver, pancreas and kidney function. Green bean, oolong tea and cinnamon are plants that can lower cholesterol levels. Oolong tea contains catechins, Green Bean contain phytosterols and cinnamon contains cinnamaldehyde. Determination of secondary metabolite levels of extracts was carried out using the Liquid Chromatography – Mass Spectroscopy (LC-MS) method. The activity test was carried out with 30 Wistar white rats which were divided into 6 test groups. The normal control group was treated with CMC-Na without feeding hypercholesterolemia, the positive control group was treated with simvastatin 0.4 mg/KgBW, the negative control group was treated with CMC-Na, the test groups 1, 2 and 3 were treated with cinnamon extract, oolong tea and green bean, respectively (150:50:50 mg/KgBW), (50:150:50 mg/KgBW) and (50:50:150 mg/KgBW). The detected metabolite content was cinnamaldehyde in cinnamon up to 10%, catechins in oolong tea up to 12% and stigmasterol in beans as much as 3.4%.The results obtained by test group 1 and test group 2 can reduce cholesterol and triglyceride levels (p0.05). All test groups had no significant effect on HDL and LDL levels.